Between Social Clamors, Internal Divisions and the Far-right: the Traditional Chilean Right in the 2021 Presidential Elections - Zhao, Xi (2026)
This paper analyzes the programmatic response of the traditional Chilean right in the 2021 presidential elections, within the post-2019 social uprising electoral context, alongside the electoral rise of the radical right. Through discourse analysis of candidate Sebastián Sichel during the campaign, it examines how the center-right responded electorally to massive social demands and the reconfiguration of the party system. The findings reveal an attempt to incorporate liberal-reformist elements: openness toward a more solidarity-based state role in social rights, progressive positioning on moral and environmental issues, and distancing from the Pinochet regime. However, the research shows that the traditional right maintained convergent positions with the far right on central aspects: defense of subsidiarity, emphasis on public order and security, and activation of anti-communist discourse. It is concluded that, despite specific differences, there exists a porous boundary between both rights, explained by their historical and ideational connections. The center-right's electoral response, marked by internal tensions, far from constructing an alternative that addressed popular concerns manifested during the uprising, ended up validating the legitimacy of the ultraconservative agenda, thus contributing to the electoral consolidation of the radical right in Chile.